2007
DOI: 10.1074/jbc.m705224200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Knockdown of Protein-tyrosine Phosphatase 1B by 1,2-Naphthoquinone through Covalent Modification Causes Persistent Transactivation of Epidermal Growth Factor Receptor

Abstract: 1,2-Naphthoquinone (1,2-NQ), an atmospheric contaminant, causes the contraction of guinea pig trachea through the activation of epidermal growth factor receptor (EGFR) by inhibiting protein-tyrosine phosphatases (PTPs). Phosphorylation of EGFR is negatively regulated by PTPs, but details of the mechanism by which 1,2-NQ inhibits PTPs have not been elucidated. Results described in this report demonstrate that 1,2-NQ forms covalent bonds with PTP1B after exposure to human epithelial A431 cells. In this study, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 34 publications
(27 reference statements)
8
118
0
1
Order By: Relevance
“…*Significantly different from control at p < 0.05 (ANOVA). through Cys151, Cys253, Cys273, Cys288, and Cys489, thereby activating EGFR and Nrf2 (Iwamoto et al, 2007;Kobayashi et al, 2009) because PTP1B and Keap1 are known to be negative regulators for EGFR and Nrf2, respectively (Itoh et al, 1999;Barford et al, 1995). These findings strongly indicate that 1,2-NQ is a bi-aromatic hydrocarbon that potentially activates EGFR and Nrf2 following covalent modification of PTP1B and Keap1 protein, respectively, through these thiol groups.…”
Section: Discussionmentioning
confidence: 62%
“…*Significantly different from control at p < 0.05 (ANOVA). through Cys151, Cys253, Cys273, Cys288, and Cys489, thereby activating EGFR and Nrf2 (Iwamoto et al, 2007;Kobayashi et al, 2009) because PTP1B and Keap1 are known to be negative regulators for EGFR and Nrf2, respectively (Itoh et al, 1999;Barford et al, 1995). These findings strongly indicate that 1,2-NQ is a bi-aromatic hydrocarbon that potentially activates EGFR and Nrf2 following covalent modification of PTP1B and Keap1 protein, respectively, through these thiol groups.…”
Section: Discussionmentioning
confidence: 62%
“…Instead, the interesting possibility exists that each compound reacts with specific target proteins unrelated to the Keap1-Nrf2 system through specific cysteine residues. Indeed, the class 2 compound 1,2-NQ was reported to target Cys-121 in protein tyrosine phosphatase 1B (PTP1B) (14). Emitted as one of combustion products of fossil fuels and also formed in the atmosphere by photochemical reactions of aromatic hydrocarbons, 1,2-NQ is considered to create a variety of hazardous effects in vivo, including acute cytotoxicity, immunotoxicity, and carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were mixed with ␣-cyano-4-hydroxycinnamic acid (2.5 mg/ml) containing 50% acetonitrile and 0.1% trifluoroacetic acid and dried on stainless steel targets at room temperature. Analyses were performed using an AXIMA-TOF2 (Shimadzu) with a nitrogen laser, as described previously (14). All analyses took place in the positive ion mode, and the instrument was calibrated immediately prior to each series of studies.…”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, we prepared a specific antibody against 1,2-NQ. 18) This antibody can recognize 1,2-NQ, 1,2-dihydroxynaphthalene, 1,2-NQ-4-mercaptoethanol adduct and 1,2-NQ-4-sulfonate, but not 1,4-NQ, and found that there were cellular proteins modified by 1,2-NQ. This suggests that 1,2-NQ exhibits not only redox but also electrophilic characteristics.…”
Section: Disruption Of Signal Transduction Through Covalent Modificationmentioning
confidence: 99%
“…As expected, a concentration-dependent phosphorylation occurring during exposure of A431 cells to 1,2-NQ was found to be coupled to the reduction of PTP activity in the cells; under these conditions, 1,2-NQ did bind to PTP1B among cellular PTPs. 18) In cell-free systems, matrix-assisted laser desorption and ionization time-of flight mass spectrometry (MALDI-TOF/MS) analysis revealed that 1,2-NQ is covalently bound to Cys121, thereby causing reduction of the catalytic activity. Thus, we concluded that covalent modification of 1,2-NQ to PTP1B is at least partially responsible for the reduction of PTP activity, which leads to prolonged phosphorylation of EGFR in A431 cells.…”
Section: Disruption Of Signal Transduction Through Covalent Modificationmentioning
confidence: 99%